Le fratture di gamba in età pediatrica - Alberghina, F.; Andreacchio, A. (Lo Scalpello - Journal, 2018)
PAEDIATRIC DIAPHYSEAL FRACTURES OF TIBIA AND FIBULA Diaphyseal fractures of tibia and fibula are common in children and adolescents. Radiographic evaluation should be accompanied by meticulous neurovascular status monitoring. Closed reduction and casting are still a good option in undisplaced fractures affecting young children, although flexible intramedullary nailing has become increasingly popular for fractures that require surgical fixation.